دراسة التأثير الأليلوباثي للمستخلصات المائية والمسحوق الجاف لعشبة الحلفا Imperata cylindrica L. في نمو غراس الزيتون - طباش, سمير; عشي, ميرنا; زيني, سماح (Latakia University Journal -Biological Sciences Series, 2018)
تم إجراء هذه الدراسة لتحديد التأثير الأليلوباثي (التضاد البيوكيميائي ) لعشبة الحلفا Imperata cylindrica في نمو غراس الزيتون Olea europea L. بعمر سنة واحدة، في ظروف المشتل، وقد اعتمد في هذه الدراسة على تجربتين. تم خلال التجربة الأولى، دراسة تأثير المستخلصات المائية لأوراق وجذور وريزومات الحلفا، بالتراكيز التالية 2%،4 %، %8في بعض مؤشرات نمو غراس الزيتون ( طول وقطر الغراس) ، بينت النتائج أن التركيزين %4و %8 من المستخلص المائي، كان لهما تأثير مثبط في نمو الغراس، حيث انخفض معدل الطول بنسبة %60.2 و%83 على التوالي بالنسبة لطول الشاهد، لوحظ عند التركيز 2% تأثيراً محفزاً للنمو، حيث زاد معدل النمو الطولي للغراس بنسبة 31.5% مقارنة بالشاهد. أما بالنسبة لمعدل نمو قطر الغراس فكان متوافقاً مع معدل النمو الطولي، فعند التركيز2 % كان التأثير الأليلوباثي محفزاً للنمو، وزاد معدل نمو القطر بمقدار %56.8، بينما لوحظ تأثيراً مثبطاً عند التركيزين %4 و8%، حيث انخفض معدل نمو القطر بنسبة %80 و%91.5 على التوالي. وفي التجربة الثانية، تمت دراسة التأثير الأليلوباثي لإضافة المسحوق الجاف لأوراق وجذور وريزومات الحلفا بالتراكيز 2%، 4%،8 %، إلى تربة أصص زراعة الغراس، على طول وقطر الغراس. بينت النتائج أن التركيزين %4و %8من المسحوق الجاف، كان لهما تأثير أليلوباثي مثبط لنمو الغراس، حيث انخفض معدل الطول بنسبة %50.3و 80% على التوالي. وقد كان تأثير إضافة المسحوق بتركيز 2% منشط لنمو الغراس، حيث بلغت نسبة الزيادة 23%، ولكن بنسبة أقل من تأثير المستخلصات المائية. وكان هذا التأثير متوافقاً مع زيادة معدل نمو الأقطار، حيث لوحظ وجود تأثير محفز لنمو الأقطار، عند التركيز %2بنسبة 27.9% مقارنة بالشاهد، وأصبح مثبطاً للنمو عند التركيزين %4و %8بمقدار 62.7% و88% على التوالي. بينت النتائج أن مستخلصات الحلفا المائية والمسحوق الجاف تحوي مواد كيميائية ذات تأثير أليلوباثي تفسر قدرتها التنافسية العالية مع المحاصيل الأخرى، وازداد التأثير المثبط بزيادة التركيز. This study was designed to estimate the allelophatic effect of cogongrass (Imperata cylindrica L.), in the growth of one year old of olive seedlings, in a nursery (greenhouse) conditions. Two experiments were conducted in this study. In the first experiment, the effect of the aqueous extracts of cognograss leaves, rhizomes, and roots, at concentrations of (2%, 4% and 8%) on the growth of olive seedlings (total length and diameter) were evaluated. The results of this experiment indicated an inhibitory effect of the 4% and 8% aqueous extracts on growth parameters. It was found that treatments with 4% and 8% aqueous extracts caused significant reduction (60.2% and 83%) respectively in the total length, in compare to the control. As for the 2% aqueous extract, it showed a stimulation effect in the growth, an increase about 31.5% was recorded for the total length in compare to the control. A similar result was observed in regard the seedlings diameter growth. The 2% aqueous extract showed an 56.8% increase in the rate of diameter growth, while the 4% and 8% extracts showed a reduction effects 80% and 91.5% respectively. The second experiment evaluated the effect of dried powder of cogongrass parts at concentrations of (2%, 4% and 8%) on the growth of olive seedlings. The results indicated the allelophatic effect of 2%, 4% and 8% dried leaves, roots and rhizomes powder on the growth of olive seedlings (total length and diameter). The results indicated an Allelopathic effect of 4% and 8% dried parts added to pot soils on the growth of olive seedlings (total length and diameter). The 4% and 8% dried powder reduced the total length by 50.3% and 80% respectively. The effect of the 2% dried leaves and roots powder increased the growth of the seedlings, but was less than the 2% aqueous extract, the increase rate of growth was 23% for the powder and 31.5% for the aqueous extract. As for the diameters growth rate, the results indicate an increase of the diameters growth 27.9% when treated with 2% of the dried powder, and the treatments with 4% and 8% showed a reduction of growth by 62.7% and 88% respectively. Results indicate that aqueous extracts and dried powder of cogongrass may contain allele chemicals that may contribute to its invasiveness and extreme competitiveness.